Assessing university student's Van Hiele level of abstract thinking in-two variable linear equations using IRT: Implication for Economic Education - Irwanto, Jesi; Kurniati, Dian; Yudianto, Erfan; Santoso, Kiswara Agung (International Journal of Innovative Research and Scientific Studies, 2025)
This study aimed to identify and analyze the level of students' abstract thinking related to systems of two-variable linear equations using van Hiele's theory within the Item Response Theory (IRT) framework. This quantitative study involved 139 Indonesian students selected through random sampling. The research instrument, which was compiled based on the five van Hiele levels, was analyzed using SPSS and R Studio. The results showed that there were 8 students at level 0, 35 at level 1, 12 at level 2, 29 at level 3, and 15 at level 4. In addition, 23 students were in the transition stage, and 16 students could not be classified. The research findings indicate a significant gap in students' abstract thinking abilities, which suggests the need for a learning approach that encourages higher-level reasoning. The conclusion is that most students are at the analysis level; therefore, an appropriate learning approach is needed to develop students' abstract thinking abilities in systems of two-variable linear equations. The implication of an appropriate approach is that it will better prepare students, especially in the field of economics, to apply mathematical models in research.